Implementasi Theory of Planned Behavior dalam Mendeteksi Whistle-Blowing Intentions di Sektor Publik - Amrullah, Muhammad Mukhlis; Kaluge, David (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
This study aimed to examine the effect of attitudes, subjective norms, behavioral control on behavioral intention as well as the effect of behavioral intention on whistle-blowing intentions. This research was conducted at all government unit offices in the Municipality of Probolinggo which is called SKPD by using a questionnaire. Survey responses collected from a sample of 65 staffs in the financial section within SKPD represented by the chief financial officer and treasurer. The findings indicate that all of the variables in the TPB, such as attitude, subjective norms and behavioral control has a significant effect on whistle-blowing intentions. The implications of this research provided recommendation and consideration in analyzing the tendencies of whistle-blowing that can be performed by government staff. In general, we view that the implementation of whistleblowing as an internal policy would exhibit organizational support and thus, enhances staffs’ attitude towards whistle-blowing. Keywords: attitude, subjective norms, behavioral control, intention, whistle-blowing intentions, public sector, theory of planned behavior.